Anatomy of the cardiac conduction system - Padala, Santosh K.; Cabrera, José‐Angel; Ellenbogen, Kenneth A. (Pacing and clinical electrophysiology, 2021)
The specialized cardiomyocytes that constitute the conduction system in the human heart, initiate the electric impulse and result in rhythmic and synchronized contraction of the atria and ventricles. Although the atrioventricular (AV) conduction axis was described more than a century ago by Sunao Tawara, the anatomic pathway for propagation of impulse from atria to the ventricles has been a topic of debate for years. Over the past 2 decades, there has been a resurgence of conduction system pacing (CSP) by implanting pacing leads in the His bundle region in lieu of chronic right ventricular pacing that is associated with worse clinical outcomes. The inherent limitations of implanting the leads in the His bundle region has led to the emergence of left bundle branch area pacing in the past 3 years as an alternative strategy for CSP. The clinical experience from performing CSP has helped electrophysiologists gain deeper insight into the anatomy and physiology of cardiac conduction system. This review details the anatomy of the cardiac conduction system, and highlights some of the recently published articles that aid in better understanding of the AV conduction axis and its variations, the knowledge of which is critical for CSP. The remarkable evolution in technology has led to visualization of the cardiac conduction system using noninvasive, nondestructive high‐resolution contrast‐enhanced micro‐computed tomography imaging that may aid in future CSP. We also discuss from anatomical perspective, the differences seen clinically with His bundle pacing and left bundle branch area pacing.